THE EFFECT OF THERAPEUTIC COMMUNICATION TO THE ANXIETY IN FACING RETIREMENT FOR PRE ELDERLY (STUDIED IN THE VILLAGE OF DEMPELAN DISTRICT OF MADIUN, MADIUN REGENCY) - Veni Medika Sari; Asrina Pitayanti; Iva Milia Hani Rahmawati (STIKES Insan Cendekia Medika Jombang, 2012)
Retirement should make people happy because they can enjoy their elderly. But otherwise retirement is oftenestimated as a reality that can not be satisfied so before the time comes partially the people fell worriedbecause they do not know what kind of life they will face later. The purpose of this research was to know theeffect of therapeutic communication to the elderly anxiety in facing retirement to the pre elderly in the villageof Dempelan district of Madiun Madiun regency.This research design was one group pre test post tetsdesign. The population was all employers who would experience retirement in the village of Dempelandistrict of Madiun Madiun regency was a number of 12 people. The sampling technique used was totalsampling with the sample a number of 12 people. The variable in this research consisted of independentvariable that’s therapeutic communication and the dependent variable was the anxiety in facing retirement tothe pre elderly. The research instrument used questionnaire with data processing by editing, coding, scoring,tabulating and the statistic test used wilcoxon. The research result showed that’s most of anxiety in facingretirement which given therapeutic communication was moderate amounted 7 respondent (58,3%) and mostof anxiety in facing retirement which given therapeutic communication was normal amounted 8 respondent(66,7%). The test of wilcoxon showed that’s the significant value of  = 0,000 <  (0,05), so H0 rejected andH1 accepted. The conclusion is that there’s relation of therapeutic to the elderly anxiety in facing in facingretirement to the pre elderly in the village of Dempelan district of Madiun Madiun regency.